Answer:
(-
,
)
Explanation:
Given the2 equations
6 - 2x = y → (1)
14 + 3x = y → (2)
Substitute y = 14 + 3x into (1)
6 - 2x = 14 + 3x ( subtract 3x from both sides )
6 - 5x = 14 ( subtract 6 from both sides )
- 5x = 8 ( divide both sides by - 5 )
x = -
![(8)/(5)](https://img.qammunity.org/2022/formulas/mathematics/college/y7s1cglcrhxdbowsy4xxycey612v1jgjuq.png)
Substitute x = -
into either of the 2 equations for the corresponding value of y
Substituting into (1)
y = 6 - 2(-
) =
+
=
![(46)/(5)](https://img.qammunity.org/2022/formulas/mathematics/high-school/7465std2n0u3qcv5o1jryovb75twuingyq.png)
solution is ( -
,
)